Phytohormone Abscisic Acid Improves Spatial Memory and Synaptogenesis Involving NDR1/2 Kinase in Rats - Liu, Juanjuan; Gu, Xiaozhen; Zou, Rongxin; Nan, Wenping; Yang, Shaohua; Wang, Hui-Li; Chen, Xiang-Tao (Frontiers in Pharmacology, 2018)
The abscisic acid (ABA) is a phytohormone involved in plant growth, development and environmental stress response. Recent study showed ABA can also be detected in other organisms, including mammals. And it has been reported that ABA can improve learning and memory in rats. In this study, we attempted to investigate the effects of ABA on the alternation of dendritic spine morphology of pyramidal neurons in developmental rats, which may underlie the learning and memory function. Behavior tests showed that ABA significantly improved spatial memory performance. Meanwhile, Golgi-Cox staining assay showed that ABA significantly increased the spine density and the percentage of mushroom-like spines in pyramidal neurons of hippocampus, indicating that ABA increased dendritic spine formation and maturation, which may contribute to the improvement of spatial memory. Furthermore, ABA administration increased the protein expression of NDR1/2 kinase, as well as mRNA levels of NDR2 and its substrate Rabin8. In addition, NDR1/2 shRNA prohibited the ABA-induced increases in the expression of NDR1/2 and spine density. Together, our study indicated that ABA could improve learning and memory in rats and the effect are possibly through the regulation of synaptogenesis, which is mediated via NDR1/2 kinase pathway.